Administrative Challenges in Healthcare: A Review of the Effects on Medical Workers - Andy (Jurnal Manajemen, 2026)
Healthcare administrative challenges affect medical workers' morale, well-being, and productivity. Stress, burnout, and job dissatisfaction are driven primarily by excessive documentation, regulatory compliance, and inefficient electronic health records (EHRs), especially by nurses and primary care physicians. To help understand the effects of administrative pressures and explore mitigation strategies, this narrative review synthesizes findings from 23 studies published between 2020 and 2024. Initially, EHRs were designed to streamline workflow and enhance data accessibility; however, they frequently resulted in inefficiencies. Medical professionals, including physicians and nurses, recognized prevalent frustrations associated with usability challenges, alert weariness, and extended after-hours documentation. Documentation consumes considerable time, particularly in nursing and psychiatric care, with substantial documentation requirements, intense time constraints, and reduced professional satisfaction. Emotional exhaustion and depersonalization are further aggravated by poorly designed EHR systems, extended off-hours documentation, inadequate training, and deficient technological support, which have also been linked to increased turnover intentions. Mitigation strategies include increasing EHR usability, distributing non-clinical work, eliminating redundant documentation, and happy leadership. The findings underscore that the primary problem is to ascertain how to effectuate systemic reforms that alleviate administrative difficulties for healthcare workers and enhance the sustainability of the healthcare system. Future interventions must prioritize healthcare personnel's well-being to ensure high-quality care and organizational efficiency.